1989
DOI: 10.2172/10171840
|View full text |Cite
|
Sign up to set email alerts
|

Basic radiological studies contamination control experiments

Abstract: This book wall I:)nllNu'edali in account of work sponsored by en a_iency of the United States Goverrtment. NeitP_erthe United $tatu Government nor any agency thereof, nor any of their employeeS, rr_kes any werrsrtty, exlocess or imDlied, or assumes any legal iilbility or rt_:onsibi_ity for the eccurecy, completeness, or usefulnus of any _nform_tion, OPl_ratul, product or f_roceu discJosed, or re_rwents Chatits us_ wouJd ., t_ot infringe DrivateiV own_ rightS. Refer_c_ herein to any sl:mcific commercial 13roduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bench-scale tests conducted at the Idaho National Engineering Laboratory showed that chemical dust suppressants are effective for controlling dast spread (Winberg and Wixom 1992, Duce et al 1989, and Duce et al 1988. Chelnical dust suppressants, or crusting agents, may produce a tough surface without the need for repeated application" therefore, they will be tested tor applicability in the 100 Area for inactive areas.…”
Section: Crusting Agentsmentioning
confidence: 99%
“…Bench-scale tests conducted at the Idaho National Engineering Laboratory showed that chemical dust suppressants are effective for controlling dast spread (Winberg and Wixom 1992, Duce et al 1989, and Duce et al 1988. Chelnical dust suppressants, or crusting agents, may produce a tough surface without the need for repeated application" therefore, they will be tested tor applicability in the 100 Area for inactive areas.…”
Section: Crusting Agentsmentioning
confidence: 99%
“…Bench-scale tests conducted at the Idaho National Engineering Laboratory showed that chemical dust suppressants are effective for controlling dust spread (Winberg and ' Wixom 1992;Duce et al 1989;and Duce et al 1988). Chemical dust suppressants, or crusting agents, may produce a tough surface without the need for repeated application; therefore, they will be testt:d for applicability in the 100 Area for inactive areas.…”
Section: Crusting Agentsmentioning
confidence: 99%